PRACTICES ADOPTED BY FAMILIES FOR PROVIDING CLOTHING FOR CHILDREN (3-8 YEARS) IN RURAL AREA OF IKWO LOCAL GOVERNMENT AREA, EBONYI STATE, NIGERIA - Benedette , Akubue; Calister , Nwadi; Esther , David; Veronica , Imaku; Mary , Nwodo; Chinyere , Omebe (Journal of Advanced Sociology, 2022)
Purpose: The study investigated the clothing selection practices for children among families in Ikwo Local Government Area, Ebonyi State, Nigeria. Three specific purposes such as to identify (1) The People that select clothing for children in Ikwo local government area. (2) The factors considered by the families while selecting clothing for children in the area of study (3) features considered by the families while selecting clothing for the children were stated. Three corresponding research questions and two null hypotheses which were tested at 0.05 level of significance guided the study. Methodology: A structured questionnaire was used and the questionnaire was validated by three experts. Cronbach Alpha reliability test which yielded 0.89 was applied. The population was 214, 969 members of families. Multi-stage sampling technique (Yaro Yamen sampling techniques, proportionate stratified random sampling, and purposive sampling techniques) were used to select sample size of 200 respondents. Mean statistic and standard deviation were used to analyze data. Results: Finding showed that only fathers and mothers select clothing for children in Ikwo local government area. many factors and features such as climate change fashion in vogue, colour of the clothes texture and set of the fabric among others are not considered while selecting clothes for children in the area of study. Recommendation: Based on the findings, recommendations were made that economic empowerment programme sponsored by Ebonyi State government should be extended to Ikwo local government area and that Home Economists in Ebonyi State should carry out enlightenment talk on the right ways to select clothing for children in the area of study.